2009
DOI: 10.1016/j.ijnonlinmec.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial stress analysis and prediction of debonding for a thin plate bonded to a curved substrate

Abstract: This paper focuses on the analytical and numerical modeling of the interface between a rigid substrate with simple constant curvature and a thin bonded plate. The interfacial behavior is modeled by independent cohesive laws in the normal and tangential directions, coupled with a mixed-mode fracture criterion. The newly developed analytical model determines the interfacial shear and normal stress distributions as functions of the substrate curvature, during the various behavioral stages of the interface prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This predicts that debonding occurs at a strain of 2430 µstrain for the north arch (with 3 strengthening plates), or 2164 µstrain for the south arch (with 6 strengthening plates). This result also agrees with the anchorage model by De Lorenzis and Zavarise [37], who demonstrated that the curvature does not significantly affect the load at the onset of peeling.…”
Section: Strengthening Mechanisms and Modes Of Failuresupporting
confidence: 92%
“…This predicts that debonding occurs at a strain of 2430 µstrain for the north arch (with 3 strengthening plates), or 2164 µstrain for the south arch (with 6 strengthening plates). This result also agrees with the anchorage model by De Lorenzis and Zavarise [37], who demonstrated that the curvature does not significantly affect the load at the onset of peeling.…”
Section: Strengthening Mechanisms and Modes Of Failuresupporting
confidence: 92%
“…Despite the first models have been developed for single-mode fracture processes, cohesive fracture is expected to involve mixed-mode conditions, as observed in practice by experimental investigations performed on various types of lap joints [35], or interfaces between FRP sheets and flat [36,37] or curved substrates [38,39]. Mixed-mode CZMs can be classified as http://dx.doi.org/10.1016/j.engfracmech.2015.09.029 0013-7944/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…There are many models in the literature to calculate the s b distribution and their maximum, which is herein denoted by s bM [2][3][4]6,9,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, durability of a RC member externally reinforced with FRP depends not only on durability of the individual materials, but also on the capacity of the concrete cover to sustain the bond stresses s b [22][23][24][25]. In fact, on one hand, the FRP-composite material keeps its original strength, elasticity, and toughness [5,13,15,16,[26][27][28]; on the other hand, however, the combination of s b and initial cracks (flaws) in the concrete cover may give rise to slow crack growth up to the critical length, and eventually to debonding of the external reinforcement [29][30][31][32][33][34][35][36]. Unfortunately, neither the structural codes nor the structural practice considers explicitly the service failure that is caused by slow crack growth in the concrete cover.…”
Section: Introductionmentioning
confidence: 99%